Genotype-Phenotype Correlations in Neurofibromatosis and Their Potential Clinical Use. Issue 7 (17th August 2021) - Bettegowda, Chetan; Upadhayaya, Meena; Evans, D. Gareth; Kim, AeRang; Mathios, Dimitrios; Hanemann, Clemens O.
Abstract : Objective: Because clinically validated biomarkers for neurofibromatosis 1 (NF1) and neurofibromatosis 2 (NF2) have not been identified, we aimed to determine whether genotype-phenotype correlations are useful in clinical trials in NF1 and NF2. Methods: The Response Evaluation in Neurofibromatosis and Schwannomatosis (REiNS) Biomarker Group first performed a systematic literature search and reviewed existing data on genetic biomarkers in NF1 and NF2 and in in malignant peripheral nerve sheath tumors. The group then met during a series of consensus meetings to develop a joint report. Results: We found that in NF2, the genetic severity score is clearly of potential clinical use. In NF1, despite over 3, 000 constitutional variants having been described in the NF1 gene, only 4 actionable genotype-phenotype correlations exist. The diagnosis and treatment decision of these tumors should ideally include histopathology and compilation of some of the genetic markers. Conclusion: We summarized emerging clinical use of genotype-phenotype correlations in neurofibromatosis.